Surgery of Trismus in Oral Submucous Fibrosis An Atlas (Springer Singapore, 2018)
This book offers an essential guide to treating trismus due to oral submucous fibrosis (OSMF) - a specific condition involving the mouth that is common in geographical areas where chewing of betel nut and tobacco is prevalent, particularly in Central India. Based on the editors' more than two decades of experience employing techniques such as platysma flap and mandibular mucoperiosteal flaps to treat trismus of OSMF, the book will help surgeons who encounter these disorders to create their own management protocols. The initial chapters detail how the authors themselves have dealt with this disorder; the following chapters consist of separate entries, each of which contains clinical photographs and a brief description. Readers can either read the atlas as a textbook, or as a reference work. The book will benefit practitioners of ENT, head and neck, maxillofacial, dental and plastic surgeries, as well as general surgeons and postgraduate students.